2023
DOI: 10.1021/acs.chemmater.2c03103
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Ion Mobility in V- and P-doped Bi2O3-Based Solid Electrolytes: Combining Quasielastic Neutron Scattering with Ab Initio Molecular Dynamics

Abstract: We report the direct observation of oxide ion dynamics on both nano-and picosecond timescales in the isostructural Bi 2 O 3 -derived solid electrolytes Bi 0.852 V 0.148 O 1.648 and Bi 0.852 P 0.148 O 1.648 using quasielastic neutron scattering. Comprehensive ab initio molecular dynamics simulations allowed us to reproduce the experimental picosecond timescale data by directly simulating the scattering function at various temperatures. Our analysis of the experimental data in conjunction with the simulations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Meanwhile they employed variable-temperature quasielastic neutron scattering (VT-QENS) to understand the dynamics of oxide ion migration on the nanosecond time scale in Bi 0.913 V 0.087 O 1.587 composition, related to the highest oxide ion conductivity among the Bi 2 O 3 -based compositions. 221,222 The results demonstrated rapid motion dynamics between two nearest-neighbor oxygen sites with 2.83 Å distance during the heating progress and the nature of translational diffusion above 300 °C, which was ascribed to the rate-determining diffusion within the fluorite-like Bi−O substructures. Yet, the diffusion associated with VO n units is too fast to be detectable through the VT-QENS technique.…”
Section: Fluorite-derived Oxide Ion Conductorsmentioning
confidence: 89%
See 3 more Smart Citations
“…Meanwhile they employed variable-temperature quasielastic neutron scattering (VT-QENS) to understand the dynamics of oxide ion migration on the nanosecond time scale in Bi 0.913 V 0.087 O 1.587 composition, related to the highest oxide ion conductivity among the Bi 2 O 3 -based compositions. 221,222 The results demonstrated rapid motion dynamics between two nearest-neighbor oxygen sites with 2.83 Å distance during the heating progress and the nature of translational diffusion above 300 °C, which was ascribed to the rate-determining diffusion within the fluorite-like Bi−O substructures. Yet, the diffusion associated with VO n units is too fast to be detectable through the VT-QENS technique.…”
Section: Fluorite-derived Oxide Ion Conductorsmentioning
confidence: 89%
“…This accounts for the optimal oxide ion conductivity found in V-doped rather than P-doped materials, and more importantly highlights the significance of the variable coordination number of V to support the oxygen exchange. In addition, Peet et al and Schwaighofer et al performed long-scale AIMD simulations, which revealed that oxygen ion migration associated with M O n ( M = V and P) polyhedral substructures takes picoseconds, which is much faster than the nanosecond time scale for the Bi–O substructures (Figure ), meaning that oxygen migration in the Bi–O substructure is the rate-limiting step. Meanwhile they employed variable-temperature quasielastic neutron scattering (VT-QENS) to understand the dynamics of oxide ion migration on the nanosecond time scale in Bi 0.913 V 0.087 O 1.587 composition, related to the highest oxide ion conductivity among the Bi 2 O 3 -based compositions. , The results demonstrated rapid motion dynamics between two nearest-neighbor oxygen sites with 2.83 Å distance during the heating progress and the nature of translational diffusion above 300 °C, which was ascribed to the rate-determining diffusion within the fluorite-like Bi–O substructures.…”
Section: Fluorite-derived Oxide Ion Conductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge in this approach has traditionally been the computational cost related to the size of the simulation box, which can realistically be probed. Nevertheless, AIMD simulations have successfully been used to elucidate ionic conduction pathways and mechanisms in oxide ion conductors belonging to a number of different structural families, including fluorites, apatites, , LAMOX, and perovskite-related materials.…”
Section: Introductionmentioning
confidence: 99%